Effect of nasal irrigation on allergic rhinitis control in children; complementarity between CARAT and MASK outcomes. Issue 1 (13th March 2020) - Mitsias, Dimitrios I.; Dimou, Maria V.; Lakoumentas, John; Alevizopoulos, Konstantinos; Sousa‐Pinto, Bernardo; Fonseca, Joao A.; Bousquet, Jean; Papadopoulos, Nikolaos G.
Abstract: Background: Nasal irrigations (NI) are increasingly used as an over‐the‐counter adjunctive treatment for allergic rhinitis (AR), but clinical studies on their effectiveness are limited. Methods: An open‐label, controlled, non‐randomized, real‐life study was conducted to evaluate the effectiveness of NI with a new hypertonic solution as add‐on treatment for AR. Children and adolescents with AR were prescribed symptomatic treatment. The active group also received an additional sea‐water NI solution supplemented with algae extracts. The primary endpoint was symptom control, assessed by the control of allergic rhinitis and asthma test (CARAT) questionnaires. Moreover, the MASK/Allergy Diary was used to track symptoms and daily medication use that were combined in a novel total symptom/medication score (TSMS). Results: We assessed 76 patients. Overall, there was a significant improvement of CARAT results (median Z‐score change of 1.1 in the active/NI group vs. 0.4 in the control group; p = 0.035). Among patients > 12 years old (n = 51), there was a significant improvement in CARAT10 results among participants receiving NI (21.0 to 25.5; p < 0.001), but not in the regular treatment group (21.5 to 24.0; p = 0.100). For children < 12 years old (n = 25), the ΝΙ group had significantly improved symptom control (CARATKids results: 5.0 to 2.0; p = 0.002), in contrast to the control group (4.0 to 2.5; p = 0.057). MASK data on allergic symptoms were comparable between groups. However, the NI group had lower TSMS, more days with < 20% symptoms and fewer days using symptomatic treatment (26.9% vs. 43.5%; p = 0.005). Conclusion: Addition of NI with a sea‐water solution to regular treatment improved AR symptom control. CARAT questionnaires and MASK application can be useful outcome tools in real‐life studies.